2018
DOI: 10.1007/978-3-319-77404-6_42
|View full text |Cite
|
Sign up to set email alerts
|

Majority Model on Random Regular Graphs

Abstract: Consider a graph G = (V, E) and an initial random coloring where each vertex v ∈ V is blue with probability P b and red otherwise, independently from all other vertices. In each round, all vertices simultaneously switch their color to the most frequent color in their neighborhood and in case of a tie, a vertex keeps its current color. The main goal of the present paper is to analyze the behavior of this basic and natural process on the random d-regular graph G n,d . It is shown that for all ǫ > 0, P b ≤ 1/2 − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…Therefore, Theorem 9 implies that in the majority model on G ∆ n , if |B(0)| ≤ ( 1 2 − c √ ∆ )n for some large constant c then the process gets fully red a.a.s. This result is already known by Gärtner and Zehmakan [17], however with a much more involved proof.…”
Section: :11supporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, Theorem 9 implies that in the majority model on G ∆ n , if |B(0)| ≤ ( 1 2 − c √ ∆ )n for some large constant c then the process gets fully red a.a.s. This result is already known by Gärtner and Zehmakan [17], however with a much more involved proof.…”
Section: :11supporting
confidence: 67%
“…The majority model has been studied on different classes of graphs, like lattice [16,36,38,15], infinite lattice [10], random regular graphs [17], and infinite trees [22], when the initial configuration is random, meaning each node is independently blue with probability p b and red otherwise (without loss of generality, we always assume p b ≤ 1/2). We are interested in the behavior of the process when the underlying graph is the Erdős-Rényi random graph G n,p , where the node set is [n] = {1, · · · , n} and each edge is added with probability p independently.…”
Section: Introductionmentioning
confidence: 99%
“…In the deterministic majority, every node updates its state according to the majority state of its neighborhood as a whole, loosing the random interaction, which is a fundamental feature of the dynamics previously discussed. This deterministic protocol has been extensively studied in the literature; we mention, for example, its analysis on expander graphs [MNT14,Zeh20], random regular graphs [GZ18], and Erdős-Rnyi random graphs [BCO + 16, Zeh20].…”
Section: Related Workmentioning
confidence: 99%
“…In particular, he proved that on a d ‐regular λ‐expander graph G , when the initial configuration satisfies vVfalse(Gfalse)S0false(vfalse)4λdn, majority dynamics will reach the configuration where every vertex has state +1 within Ofalse(normallogd2false/λ2nfalse) rounds. Also, Gärtner and Zehmakan 5 showed that if the initial density of the −1s is 1/2 − ε for some ε > 0, then the majority dynamics will eventually reach the configuration where every vertex has state +1.…”
Section: Introductionmentioning
confidence: 99%